2008
DOI: 10.2223/jped.1747
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of congenital heart disease diagnosed at birth: analysis of 29,770 newborn infants

Abstract: Methods:A retrospective, database driven study, part of the LatinAmerican collaborative study of congenital malformations. Records were reviewed on all live born (LB) and stillborn (SB) infants with congenital heart diseases diagnosed by postnatal echocardiogram or by autopsy. Data on birth weight, sex, age and parity were collected for the LB and studied for associations. The statistical analysis employed Pearson's chisquare test and multinomial logistic regression.Results: During the period studied there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
34
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 23 publications
7
34
0
3
Order By: Relevance
“…The total observed prevalence of congenital heart defects was higher than that found in other studies, 15,[20][21][22][23][24] primarily because of the large number of minor defects that were diagnosed postnatally on neonatal echocardiography. Ventricular septal defects were the most common defects, accounting for 62.7% of all cases.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The total observed prevalence of congenital heart defects was higher than that found in other studies, 15,[20][21][22][23][24] primarily because of the large number of minor defects that were diagnosed postnatally on neonatal echocardiography. Ventricular septal defects were the most common defects, accounting for 62.7% of all cases.…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, the prevalence of major defects was 3.0 per 1000, 75% of which were diagnosed prenatally by fetal echocardiography. The prenatal detection rate for minor defects was significantly lower than the rate for major defects.The total observed prevalence of congenital heart defects was higher than that found in other studies, 15,[20][21][22][23][24] primarily because of the large number of minor defects that were diagnosed postnatally on neonatal echocardiography. Ventricular septal defects were the most common defects, accounting for 62.7% of all cases.…”
mentioning
confidence: 64%
“…Two Brazilian studies analyzed prevalence of congenital heart diseases in alive newborns and identified 5.5:1,000 newborns between 1989 and 1998 3 and 9.58:1,000 newborns between 1990 and 2003 4 . These malformations can be isolated cases, part of syndromes or results of genetic diseases, such as deletion of chromosomal regions, or it can be caused by environmental factors (use of teratogenic drugs by mothers, infections during pregnancy) 5 .…”
mentioning
confidence: 99%
“…In a literature review, only two publications in English language were found with similar goal to our study, that was to evaluate presence of abdominal malformations in patients with CHD through AUS 9,10 . In contrast, our study is unique in that all CHD patients underwent AUS, high resolution karyotype and FISH for detection of microdeletion 22q11.2, and all were examined by a clinical geneticist 7,[8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Muragasu et al 10 , the patients were submitted only to the ultrasound study of the urinary tract, and 11.9% clinically significant abnormalities were found. Most of the other studies that described extracardiac malformations in patients with CHD did not indicate which methods were used to detect abdominal abnormalities, and were performed retrospectively through review of patient records 7,18,[21][22][23][24][25][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%